Problem based learning sebagai strategi meningkatkan literasi sains siswa: Studi literatur - Inayah, Devy; Solihat, Neng (Journals of Indonesian Multidisciplinary Research, 2024)
Scientific literacy is a crucial skill that students must master to face the challenges of the 21st century. However, results from the PISA assessment show that Indonesian students' scientific literacy levels remain low. One instructional model considered effective in improving scientific literacy is Problem Based Learning (PBL). This study aims to review previous research on the implementation of PBL to enhance students' scientific literacy. The method used is a literature review of 15 articles published between 2019 and 2024. The results indicate that PBL implementation can enhance students' scientific literacy across four main aspects: scientific content, scientific process, scientific context, and attitudes toward science. PBL provides contextual problem-based learning experiences that promote conceptual understanding, mastery of scientific processes, application of science in daily life, and the development of positive attitudes toward science. These findings recommend the broader implementation of PBL as an effective strategy to strengthen scientific literacy at various levels of education.